Identification of sequence motifs involved in Dengue virus–host interactions. Issue 3 (3rd March 2016) - Asnet Mary, J.; Paramasivan, R.; Shenbagarathai, R.
Abstract : Dengue fever is a rapidly spreading mosquito-borne virus infection, which remains a serious global public health problem. As there is no specific treatment or commercial vaccine available for effective control of the disease, the attempts on developing novel control strategies are underway. Viruses utilize the surface receptor proteins of host to enter into the cells. Though various proteins were said to be receptors of Dengue virus (DENV) using Virus Overlay Protein Binding Assay, the precise interaction between DENV and host is not explored. Understanding the structural features of domain III envelope glycoprotein would help in developing efficient antiviral inhibitors. Therefore, an attempt was made to identify the sequence motifs present in domain III envelope glycoprotein of Dengue virus. Computational analysis revealed that the NGR motif is present in the domain III envelope glycoprotein of DENV-1 and DENV-3. Similarly, DENV-1, DENV-2 and DENV-4 were found to contain Yxxphi motif which is a tyrosine-based sorting signal responsible for the interaction with a mu subunit of adaptor protein complex. High-throughput virtual screening resulted in five compounds as lead molecules based on glide score, which ranges from −4.664 to −6.52 kcal/Mol. This computational prediction provides an additional tool for understanding the virus–host interactions and helps to identify potential targets in the host. Further, experimental evidence is warranted to confirm the virus–host interactions and also inhibitory activity of reported lead compounds.